Tunnelling effects on lateral behavior of pile rafts in layered soil - Mu, Linlong; Huang, Maosong; Finno, Richard J. (Tunnelling and underground space technology, 2012)
► New method can be used to calculated piles adjacent to tunnelling in layered soil. ► Details of functions to calculate lateral responses of passive pile raft. ► The method is carefully verified. ► Influence of the soil stiffness ratio on lateral responses of pile rafts is studied. The Mindlin’s solution or Winkler model is often adopted to estimate the response of piles subject to ground movements induced by tunnelling in the literature. Those methods are reasonable for piles in homogeneous soil, while soil systems are usually layered in practice. This paper presents a simplified analysis method that can be used to estimate lateral responses of pile rafts subject to ground movements induced by tunnelling in layered soil. The problem is solved in two stages: firstly, using the Loganathan–Poulos solution to calculate lateral free soil movements induced by tunnelling; secondly, composing the calculated free soil movements to the pile, the governing equilibrium equations of piles are solved by the finite difference method combined with the displacement and stress solutions for asymmetric loads in layered elastic system. Also, the lateral interactions between structural members, pile–pile, pile–soil, pile–raft and soil–raft, are modeled based on the solutions for asymmetric loads in layered elastic system in the method presented herein. The proposed method is verified using published results, centrifuge tests results and displacement-controlled finite element method results. The study shows that the proposed method can reasonably estimate the lateral responses of pile rafts induced by tunnelling. Additionally, the influence of soil stiffness variation is discussed. The study shows the maximum deflections and bending moments appear near the spring line of the tunnel. And the lateral behaviors of the piles are more significantly influenced by the stiffness of the underlying soil which the tunnel located in than the stiffness of the overlying soil.